2021
DOI: 10.1109/access.2021.3117120
|View full text |Cite
|
Sign up to set email alerts
|

User Stress in Artificial Intelligence: Modeling in Case of System Failure

Abstract: The uninterrupted operation of systems with artificial intelligence (AI) ensures high productivity and accuracy of the tasks performed. The physiological state of AI operators indicates a relation with an AI system failure event and can be measured through electrodermal activity. This study aims to model the stress levels of system operators based on system trustworthiness and physiological responses during a correct AI operation and its failure. Two groups of 18 and 19 participants took part in the experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The user experience of AI drawing tools not only impacts the creative process of designers but also plays a crucial role in the tools' continuous using intention and development. The study by Bitkina, Kim, Park, Park, and Kim [15] investigated the effects of system failures on operator stress levels, highlighting the importance of reliability and user-friendliness in the design of AI tools. Additionally, although the focus of the research by [16] was not on drawing tools, their discussion on the application of AI in software engineering provides valuable insights into how to enhance the user experience of AI tools, particularly in solving complex problems and automating task processing.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The user experience of AI drawing tools not only impacts the creative process of designers but also plays a crucial role in the tools' continuous using intention and development. The study by Bitkina, Kim, Park, Park, and Kim [15] investigated the effects of system failures on operator stress levels, highlighting the importance of reliability and user-friendliness in the design of AI tools. Additionally, although the focus of the research by [16] was not on drawing tools, their discussion on the application of AI in software engineering provides valuable insights into how to enhance the user experience of AI tools, particularly in solving complex problems and automating task processing.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The authors of [65] discusses how AI-based systems replacing human decision making can result in unintended consequences due to the complexity and unpredictability of algorithm-based decisions. The authors of [87] suggested that AI failures and unreliability can increase stress due to low trust in AI operations resulting from unpredictable AI reactions. Furthermore, Ref.…”
Section: Controversy and Implications: The Tessa Chatbot Incident And...mentioning
confidence: 99%